Precipitation–Flotation Process for Molybdenum and Uranium Separation from Wastewater - Yanfang Huang; Sa Yue; Aohua Li; Hu Sun; Yizhuang Wang; Qunzhen Bu; Bingbing Liu; Guihong Han (Metals)
The mining of molybdenum and uranium ores inevitably results in the generation of large volumes of wastewater containing low concentrations of metals, which poses significant threats to the environment. This study presents a novel precipitation–flotation process for the simultaneous separation of molybdenum and uranium from wastewater. A systematic investigation was conducted on the impacts of the type of precipitant, flotation reagent type, and flotation parameters on the experimental results. Ferric salt served better as a precipitant than aluminum salt and humic acid did, and sodium dodecyl sulfate (SDS) was more suitable than sodium dodecyl benzene sulfonate for acting as a surfactant and foaming agent. Under specific conditions, including a pH of 6.6, an Fe3+ dosage of 0.6 mmol·L−1, an SDS dosage of 40 mg·L−1, an air flow rate of 25 mL·min−1, and a flotation time of 10 min, the removal efficiencies of molybdenum and uranium reached 96.6% and 93.6%, respectively. After flotation, the molybdenum concentration, uranium concentration, chemical oxygen demand, and turbidity of the treated water all meet the emission standards. Furthermore, the metal removal mechanisms, including the particle size distribution, functional group structure, surface element composition, microstructure, and element distribution, were elucidated on the basis of characterization of the precipitation–flotation products.